Myths and Numbers on Whistleblower Rewards - Theo Nyreröd; Giancarlo Spagnolo (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2018)
Whistleblower rewards have been used extensively in the US to limit procurement fraud and tax evasion, and their use has been extended to fight financial fraud after the recent financial crisis. In Europe there is currently a debate on their possible introduction, but authorities appear considerably less enthusiastic than their US counterparts. While it is important that these tools are scrutinized by a lively democratic debate, many things have been written, even by important institutional players, that have no empirical backing or that are in open contrast with the available evidence from independent research. In this paper we review some of the most debated issues regarding the potential benefits and costs of financial incentives whistleblowers trying to separate existing empirical evidence from conjectures with no empirical support, and myths in obvious contrast with available evidence.
Keywords: C92; D04; G28; K42; 330; whistleblowers; rewards; economic crime; tax evasion; corruption